2004
DOI: 10.1111/j.1365-2524.2004.00510.x
|View full text |Cite
|
Sign up to set email alerts
|

Bridging the language barrier: the use of interpreters in primary care nursing

Abstract: Language barriers present a major obstacle to minority ethnic communities accessing primary healthcare. Whereas it is recognised that interpreting services are generally inadequate and inappropriate reliance is placed on family members to interpret, little is known about how nurses working in primary care utilise interpreters to overcome language barriers. The present paper reports on a study examining the utilisation of interpreting services by a range of primary care nurses from the perspectives of the nurse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

13
130
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 136 publications
(145 citation statements)
references
References 8 publications
13
130
2
Order By: Relevance
“…This is in accordance with what Gerrish and co-workers [43] reported, and they also found that professionals in health-care were reluctant to use interpreters in the encounter with minority ethnic groups. Even if the presence of family members is important for supporting older immigrants in their contact with the health care system [44] , the utilization of professional interpreters is also of outmost importance [37] .…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…This is in accordance with what Gerrish and co-workers [43] reported, and they also found that professionals in health-care were reluctant to use interpreters in the encounter with minority ethnic groups. Even if the presence of family members is important for supporting older immigrants in their contact with the health care system [44] , the utilization of professional interpreters is also of outmost importance [37] .…”
Section: Discussionsupporting
confidence: 90%
“…Even if the presence of family members is important for supporting older immigrants in their contact with the health care system [44] , the utilization of professional interpreters is also of outmost importance [37] . However, Gerrish et al [43] have highlighted that both nursing personnel and doctors need training in how to collaborate with interpreters, so the communication can run smoothly between the triad of patient, professional and interpreter. Other ways to aid communication with minority ethnic groups in health care has been described such as including family members who can translate and write down usable words and phrases [44] , or using multilingual staff in nursing homes [45] .…”
Section: Discussionmentioning
confidence: 99%
“…Apart from the religious and cultural determinants reported in this study, other factors such as poverty and ignorance have been identified in a similar study in Nigeria (Onyigbuo et al, 2015), which confirms the role of social capital in health seeking among developing countries (Gerrish, Chau, Sobowale & Birks, 2004), with unavailable, inadequate, expensive or unaffordable medical services. However, the importance attached to the pre-migration impact of poverty in healthcare utilisation among immigrant Nigerians was based on its continued role in view of a free medical service (NHS) at the point of entry.…”
Section: Discussionsupporting
confidence: 84%
“…An individual's ability to communicate may decrease during illness and the weakness is accentuated by cultural and language differences in the encounter [6]. The competence of the interpreter is thus crucial [7]. GPs, especially those working in immigrant areas, must try to obtain familiarity in working effectively with an interpreter and be aware of the interpreterÁpatient interaction [8,9].…”
mentioning
confidence: 99%